1984
DOI: 10.1002/nau.1930030304
|View full text |Cite
|
Sign up to set email alerts
|

Effect of metoclopramide on ejaculatory threshold in a group of premature ejaculators

Abstract: The exact etiology of premature ejaculation is not known. Recent data using rats has demonstrated that dopamine agonists can lower ejaculatory thresholds while pretreatment with substituted benzamides will block that effect. Metoclopramide, the only drug in the group available in the United States, and a placebo were given to 12 premature ejaculators in a double-blind crossover fashion. Couples had intercourse on Wednesdays and Saturdays for four weeks. Ejaculatory latencies were recorded separately by husband… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1988
1988
2007
2007

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…These reports comprised the use of anesthetic ointments, 12,26,27,[29][30][31][32][33][34][35][36][37] neuroleptics, 20,22,[38][39][40][41][42] monoamine-oxidase inhibitors, 16,43 sympatholytic drugs, 18,19,[44][45][46] antibiotics, 47,48 and a group of miscellaneous agents 13,14,21,[49][50][51] (Table 1). Between 1973 and 2003, there have been 35 studies 15,17,23-25,60-79,80,81 on daily treatment with clomipramine, a tricyclic antidepressant, and on SSRIs (Table 2).…”
Section: General Results Of Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…These reports comprised the use of anesthetic ointments, 12,26,27,[29][30][31][32][33][34][35][36][37] neuroleptics, 20,22,[38][39][40][41][42] monoamine-oxidase inhibitors, 16,43 sympatholytic drugs, 18,19,[44][45][46] antibiotics, 47,48 and a group of miscellaneous agents 13,14,21,[49][50][51] (Table 1). Between 1973 and 2003, there have been 35 studies 15,17,23-25,60-79,80,81 on daily treatment with clomipramine, a tricyclic antidepressant, and on SSRIs (Table 2).…”
Section: General Results Of Reviewmentioning
confidence: 99%
“…[33][34][35]67,76,85 Baseline periods ranged from 1 68,69 or 2 26,27 to mostly 4 weeks. 49,57,65,[77][78][79][80]89 In some studies, a certain number of intercourses 41,60,74,81 was taken as baseline measurement.…”
Section: Baseline Periodmentioning
confidence: 99%
“…Other researchers have postulated that hyperhidrosis patients' poor psychosocial adjustment may manifest itself in other psychophysiological disorders. For example, Wabrek (1984) observed that 80% of a sample of males being treated for premature ejaculation also had palmar hyperhidrosis.…”
Section: Psychophysiologic Populationsmentioning
confidence: 99%